Factor structure and measurement invariance of the University Demand-Resource Questionnaire: further evidence from Hungarian university students - Sun, Guo-Dong; Chen, Hua-Ke; Sun, Wei-Xing; Szabó, Éva; Tóth, Enikő; Hu, Jin-Chuan; Jagodics, Balázs; Liu, Jing-Dong (Frontiers in Psychology, 2024)
Purpose The present study aimed to further examine the factor structure and measurement invariance of the UDRQ among a sample of Hungarian university students. Methods Firstly, the factor structure of the UDRQ was examined among 837 Hungarian university students. Specifically, two measurement models (first-order model and second-order model) were constructed and compared. Secondly, the internal consistency reliability of the UDRQ was examined. Thirdly, measurement invariance of the UDRQ was evaluated across genders. Finally, measurement invariance of the UDRQ was evaluated across two different samples. Results It was found that the first-order model outperformed the second-order model and better represented the factor structure of the UDRQ subscales. Results of Cronbach’s alpha and Composite Reliability suggested that the internal consistency reliabilities of the two UDRQ subscales were satisfactory. Measurement invariance analysis revealed that the UDRQ measurement model was strict invariant across genders and samples. Conclusion The findings of the present study indicated that the UDRQ displayed satisfactory reliability and validity and could be used to assess demands and resources of Hungarian university students.